Women and wheels: Determinant factors for participation in the Malaysia trucking industry - Tan, Yong Heng; Xie, Wenjing (2025)
This research explores the aspects that determine women participation in entering the Malaysian trucking industry, which is heavily male dominated. Qualitative research was developed, consisting of interviews with nine respondents in logistics and trucking firms in different provinces. The results identified four major impediments that include societal perceptions and stereotypes, safety issues, male-oriented workplace cultures, and the shortage of female role models. However, a number of motivators were found to promote more involvement, such as better working conditions, gender equity corporate policies, greater safety, and informative campaigns. The study also indicates the positive impacts of women participation on operations including improved operational safety, customer satisfaction, expanded gender diversity of the workforce, women also have the potential to alleviate the driver shortage. These findings can provide practical advice to the logistics companies, policymakers, and other industry stakeholders who may need to implement certain strategies and inclusive policies. By enhancing gender diversity, it is possible to achieve a more balanced workforce to make the Malaysia trucking industry more sustainable in the long term.